Ethanol affects limbic and striatal presynaptic glutamatergic and DNA methylation gene expression in outbred rats exposed to early‐life stress. (27th November 2015) - Vrettou, Maria; Granholm, Linnea; Todkar, Aniruddha; Nilsson, Kent W.; Wallén‐Mackenzie, Åsa; Nylander, Ingrid; Comasco, Erika
Abstract: Alcohol use disorder is the outcome of both genetic and environmental influences and their interaction via epigenetic mechanisms. The neurotransmitter glutamate is an important regulator of reward circuits and implicated in adaptive changes induced by ethanol intake. The present study aimed at investigating corticolimbic and corticostriatal genetic signatures focusing on the glutamatergic phenotype in relation to early‐life stress (ELS) and consequent adult ethanol consumption. A rodent maternal separation model was employed to mimic ELS, and a free‐choice paradigm was used to assess ethanol intake in adulthood. Gene expression levels of the Vesicular Glutamate Transporters ( Vglut ) 1, 2 and 3, as well as two key regulators of DNA methylation, DNA (cytosine‐5)‐methyltransferase 1 ( Dnmt1 ) and methyl‐CpG‐binding protein 2 ( Mecp2 ), were analyzed. Brain regions of interest were the ventral tegmental area (VTA), nucleus accumbens (Acb), medial prefrontal cortex (mPFC) and dorsal striatum (dStr), all involved in mediating aspects of ethanol reward. Region‐specific Vglut, Dnmt1 and Mecp2 expression patterns were observed. ELS was associated with down‐regulated expression of Vglut2 in the VTA and mPFC. Rats exposed to ELS were more sensitive to ethanol‐induced changes in Vglut expression in the VTA, Acb, and dStr and in Dnmt1 and Mecp2 expression in the striatal regions. These findings suggest long‐term glutamatergic and DNA methylation neuroadaptations as a consequence of ELS, and show an association between voluntary drinking in non‐preferring, non‐dependent, rodents and different Vglut, Dnmt1 and Mecp2 expression depending on early‐life history. Abstract : Using a rodent maternal separation (MS) model, the study assessed the effect of early life stress (ELS) and adult voluntary ethanol drinking on expression of Vesicular Glutamate Transporter ( Vglut ) and DNA methylation‐related genes in the mesocorticolimbic circuit and dorsal striatum. The results indicated interaction effects between ELS and ethanol consumption in a gene‐dependent and region‐dependent manner, mirrored by changes in the epigenetic machinery.